(How) do medical students regulate their emotions?. Issue 1 (December 2016) - Doulougeri, Karolina; Panagopoulou, Efharis; Montgomery, Anthony
Abstract Background Medical training can be a challenging and emotionally intense period for medical students. However the emotions experienced by medical students in the face of challenging situations and the emotion regulation strategies they use remains relatively unexplored. The aim of the present study was to explore the emotions elicited by memorable incidents reported by medical students and the associated emotion regulation strategies. Methods Peer interviewing was used to collect medical students' memorable incidents. Medical students at both preclinical and clinical stage of medical school were eligible to participate. In total 104 medical students provided memorable incidents. Only 54 narratives included references to emotions and emotion regulation and thus were further analyzed. Results The narratives of 47 clinical and 7 preclinical students were further analyzed for their references to emotions and emotion regulation strategies. Forty seven out of 54 incidents described a negative incident associated with negative emotions. The most frequently mentioned emotion was shock and surprise followed by feelings of embarrassment, sadness, anger and tension or anxiety. The most frequent reaction was inaction often associated with emotion regulation strategies such as distraction, focusing on a task, suppression of emotions and reappraisal. When students witnessed mistreatment or disrespect exhibited towards patients, the regulation strategy used involved focusing and comforting the patient. Conclusions The present study sheds light on the strategies medical students use to deal with intense negative emotions. The vast majority reported inaction in the face of a challenging situation and the use of more subtle strategies to deal with the emotional impact of the incident.